A novel five-level optimized carrier multilevel PWM quad-inverter six-phase AC drive - Sanjeevikumar, Padmanaban; Blaabjerg, Frede; Wheeler, Patrick; Fedak, Viliam; Duran, Mario; Siano, Pierluigi (2016)
A novel single carrier pulse-width modulation (PWM) for a new quad-inverter configuration for multilevel six-phase asymmetrical open-winding ac converter is proposed in this article. Modularity of the circuit consist of four standard two-level voltage source inverters (VSI) with slight modifications, i.e. one additional bi-direction switch (MOSFET/IGBT) in each phase and a link to neutral with two capacitors to generate increased output levels. Furthermore, original optimal single carrier zero-shifted five-level modulation (SCZSFM) algorithm is developed for each VSI to behave as equivalent to ones, a classical five-level multilevel inverter. Moreover, feasibility of the topology allows the VSIs to provide multilevel output voltage regardless of the open-winding electrical machine configuration. Also, the developed single carrier based PWM presents a straightforward solution compared to space vector modulation approaches for real time implementation. The total electric power shared among the four dc buses and quadruples the power capability of VSIs. Complete ac drive modules are developed numerically using simulation in MATLAB/PLECS software. Observed set of results are depicted in this paper under balanced conditions to show the effectiveness of the proposal in good agreement with theoretical background. This proposal suits the need of low-voltage/high-current applications to ac tractions, electrical vehicles and ‘More-Electric Aircraft’ propulsion systems.